Metacommentary on Utopia, or Jameson's dialectic of hope. - Buchanan, Ian (Utopian Studies, 1998)
Focuses on the metacommentary, a method of engagement used by writer Fredric Jameson to analyze Utopia. Discussion on the link between Utopia and repression; How an immanent Utopia functions.